Development and testing of a cassava peeler - DWIJA L. R; GISHA G. NAIR; RAJESH P. D; Er. Prince M. V (Guide) (Tavanur 2000 Kelappaji College of Agricultural Engineering and Technology)
tuber crops carbohydrates cassava is the most utilized yuber crop as food, feed and industrial raw material
Development and testing of a cassava peeler